Design of Phase Shifters with Enhanced Selectivity and Miniaturized Size Using D-CRLH Resonator - Zhe Chen; Jingbo Wang; Jianxun Tang (International Journal of Antennas and Propagation)
This paper proposes and demonstrates a novel filtering phase shifter with a compact size and good frequency selectivity using two dual composite right/left-handed (D-CRLH) resonators. Firstly, the study analyzes the D-CRLH structure to gain insights into its unique properties, providing a physical understanding for subsequent design procedures. Then, an ad hoc systematic design procedure for the D-CRLH phase shifter is discussed in detail. Different from the traditional phase shifter, the innovative integration of D-CRLH structure in phase shifters enables its advantages in the flexible realization of good in-band frequency selectivity and compact size. This advantageous utilization of the D-CRLH structure distinguishes our proposed phase shifter from conventional implementations. Finally, to demonstrate the feasibility of the proposed structure, we design, fabricate, and measure a prototype of the filtering phase shifter with a 90° phase shift. The comparison between simulation and measurement results shows good agreement, thereby confirming the effectiveness of both the new filtering phase shifter and the presented design procedure. Through this comprehensive investigation, our work showcases a promising solution for achieving compact size, good frequency selectivity, and reliable performance in phase shifter design.